Industrialisation and The Rise of Karl Marx as an Ideological Tide - Moitra, Moulinath; Chaterjee, Akash (Journal of Advanced Research in Humanities and Social Sciences; Vol 8 No 4 (2021): Journal of Advanced Research in Humanities and Social Science, 2022)
Industrial revolution in Europe and subsequently which spread across the world was not just a scientific advancement but also a milestone in socio- political history of the world. As factories grew to be the centres of production and the with the production processes mechanised, the nature of relations and the economic diversity of classes changed substantially. With the growth of the “working class” a new phase in the political history of class, revolution, struggle began. Karl Marx propounded his theory which has continued to be a source of hypothesis to many theorists in the world, and which has created a “theorizing puzzle” in the realm of social reality. The reasons include-firstly, the ideological foundation of the theory and secondly and universal acceptance it received. With the growing class struggle as visualised in Marxian Theory, radical ideas sprung up in the social sphere. The capitalist West was uncomfortable with Marx theorizing as it hinges on the oppressiveness and emancipation of the masses (proletariats), of the emerging modern capitalist system been brought about by the industrial revolution of the 19th century in Europe and the overthrow of the system. The capitalist (bourgeoisie), sought therefore, to develop counter theories that would demystify Marx paradigms. In view of the above, Marx prepositions were too dangerous and stood in contrast to Western bourgeois ideology and the interest it represents that professes conservative reforms and orderly social change in the system hence the urgency to tame the theory. How to cite this article: Moitra M, Chaterje A. Industrialisation and The Rise of Karl Marx as an Ideological Tide. J Adv Res Humani Social Sci 2021; 8(4): 6-10.